Analysis of Green IT practices in technology-based organizations - Theis, Vanessa; Schreiber, Dusan (Revista de Administração da UFSM, 2020)
Purpose: This paper aims to analyze Green IT practices adopted by technology-based organizations. Methodology: The study had a quantitative approach and the data were collected through a questionnaire, which was answered by 105 managers working in companies in the IT sector in Brazil Findings: Evidence collected showed that companies have a reactive behavior towards Green IT because they do not have, as their strategic objective, an increase in the general perception of value that consumers have about the company, nor do they seek competitivess based on sustainable development. Originality/value: In the Brazilian research scenario, the search for the keywords “Green IT”, “Green Information Technology”, “Green IT” and “Green Information Technology” on the Scielo search platform, found only five articles, on July 15th, 2020. In a search on the SPELL portal and CAPES Portal of Journals, also on July 15th, using the aforementioned keywords, four articles were found, in addition to those already found on the Scielo portal. Such results demonstrate how the topic is still little explored in the context of research in Brazil. It is important to note that Green IT comes up as a way of combining the available resources with the sustainability and economy policies in organizations, generating benefits for the environment and companies, providing opportunities for new business platforms.